Efficacy and safety of moxibustion for patients with functional constipation: A protocol for systematic review and meta analysis - Chen, Ying (Medicine (Baltimore), 2020)
INTRODUCTION: The objective of this review is to assess the efficacy and safety of moxibustion for treating patients with functional constipation (FC). METHODS AND ANALYSIS: We will electronically search the following databases: OVID MEDLINE, EMBASE, PubMed, Web of Science, the Cochrane Central Register of Controlled Trials, Cochrane library, CINAHL, AMED, China Network Knowledge Infrastructure, Wan-fang Database, China Biomedical Literature Database, and other resources from inception to October 2019, without any language restrictions. Randomised-controlled trials will be included. The primary outcome is the improvement in mean complete spontaneous bowel movements and stool form (utilize the Bristol Stool Form Scale [BSFS]). Secondary outcomes involve the degree of difficulty in defecation, proportion of responders, mean transit time, health-related quality of life, and adverse events rate. The methodological quality will be assessed using the Cochrane risk of bias tool. RESULTS: This work will summarize clinical evidence to assess the effectiveness and safety of moxibustion treatment for FC patients. CONCLUSION: This systematic review and meta-analysis will provide current evidence of the efficacy and safety of moxibustion treating FC. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42020157955.